The organ-protective effects of nitric oxide in adult patients undergoing cardiac surgery with cardiopulmonary bypass: a systematic review and meta-analysis - Jieru Zhang; Han Zhang; Jing Wang; Tianlong Wang; Luyu Bian; Zhenzhen Li; Jian Wang; Yuan Teng; Gang Liu; Shujie Yan; Bingyang Ji (BMC Anesthesiology)
Abstract Background Postoperative organ dysfunction remains a major challenge in adult cardiac surgery with cardiopulmonary bypass (CPB), frequently involving the kidneys, heart, and lungs. These complications are primarily driven by hemolysis, ischemia-reperfusion injury, and systemic inflammation triggered by CPB. Nitric oxide (NO), known for its vasodilatory, anti-inflammatory, and antioxidant properties, has been proposed as a perioperative strategy to protect vital organs. However, evidence regarding its efficacy remains inconclusive. Methods We followed PRISMA guidelines and systematically searched PubMed, Embase, Cochrane Library, and Web of Science for randomized controlled trials (RCTs) published up to March 1, 2025. Subgroup analyses were conducted based on NO dosage and timing of administration. To explore potential effect modifiers and assess subgroup interaction, we performed meta-regression analyses. The GRADE approach was used to assess the certainty of evidence. Sensitivity analyses and publication bias assessments (funnel plots and trim-and-fill method) were also conducted to evaluate the robustness of the findings. Results Ten RCTs involving 838 patients were included. NO administration was associated with a reduced incidence of acute kidney injury (AKI) (RR: 0.78; 95% CI: 0.64–0.94; p = 0.010), and the effect remained after trim-and-fill adjustment. mechanical ventilation (MV) duration was slightly shortened (SMD: − 0.17; 95% CI: − 0.31 to − 0.02; p = 0.025), particularly with postoperative administration (SMD: − 0.39; 95% CI: − 0.67 to − 0.12; p = 0.005). NO also reduced cardiac troponin I (cTnI) levels. No significant effects were observed for low cardiac output syndrome (LCOS), mortality, intensive care unit (ICU) length of stay (LOS), or hospital LOS. Conclusion Inhaled NO may offer organ-specific benefits in adults undergoing cardiac surgery with CPB, such as reduced AKI incidence and lower cTnI levels. However, these effects did not consistently translate into improved clinical outcomes. The observed reduction in MV duration was not significant after adjusting for publication bias, suggesting a possible overestimation. Current evidence is limited by small sample sizes and small-study effects. Further large, high-quality trials in high-risk populations are needed to confirm these findings. PROSPERO registration This review was prospectively registered in PROSPERO (ID: CRD42025649095).